2020
DOI: 10.1158/1078-0432.ccr-19-0471
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus, Letrozole, and Metformin in Women with Advanced or Recurrent Endometrioid Endometrial Cancer: A Multi-Center, Single Arm, Phase II Study

Abstract: Purpose: Treatment for patients with recurrent endometrioid endometrial cancer (EEC) are limited as paclitaxel is the only second-line chemotherapy with a response rate >13%. Targeting PIK3/mTOR in combination with hormonal therapy has shown promise. The addition of metformin may enhance this response. We conducted a phase II study evaluating everolimus, letrozole, and metformin in advanced/recurrent EEC.Patients and Methods: A Simon two-stage design was employed. Women with 2 prior chemotherapy regimens for r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 36 publications
0
47
1
4
Order By: Relevance
“…Earlier studies have used cutoff values of 10% of positive tumor nuclei or cutoff values on combined staining intensity indices. 21,32,39 A cutoff of 1%, as is currently advised in breast cancer, was also inferior to the 50% cutoff value. 40 Another potential advantage of the 50% cutoff value is that it is in use for other predictive biomarkers and it is easy to apply when scoring IHC slides.…”
Section: Commentmentioning
confidence: 85%
“…Earlier studies have used cutoff values of 10% of positive tumor nuclei or cutoff values on combined staining intensity indices. 21,32,39 A cutoff of 1%, as is currently advised in breast cancer, was also inferior to the 50% cutoff value. 40 Another potential advantage of the 50% cutoff value is that it is in use for other predictive biomarkers and it is easy to apply when scoring IHC slides.…”
Section: Commentmentioning
confidence: 85%
“… 69 Subsequently, the combination of everolimus, letrozole, and metformin was investigated, since prior research had demonstrated inhibition of proliferation and induction of apoptosis with metformin. 70 A clinical benefit in half of the 54 patients with metastatic endometrioid endometrial cancer was seen, with a partial response in 28% and stable disease in 22% after 16 weeks of therapy. However, the addition of metformin to the combination did not appear to improve the outcomes.…”
Section: Targeted Therapymentioning
confidence: 99%
“…However, the addition of metformin to the combination did not appear to improve the outcomes. 70 The human epidermal growth factor receptor HER2 provides critical signaling for cancer cell growth, survival, and proliferation. 39 The majority of endometrial cancers, which over-express HER2 are mainly serous or TP53-mutated cancers, including carcinosarcomas.…”
Section: Cellular Pathway Inhibitorsmentioning
confidence: 99%
“…The development of a new generation of inhibitors with greater specificity and fewer side effects is strongly warranted for the management of EC [31]. The combination of aromatase inhibitors with mammalian target of rapamycin (m-TOR) inhibitors (such as everolimus), and of aromatase inhibitors with m-TOR inhibitors and metformin could offer promising perspectives of clinical research [32-34]. The employment of the cyclin-dependent kinase 4/6 inhibitor palbociclib in EC is still investigational [35].…”
Section: Role Of Htmentioning
confidence: 99%